Green energy : technology, economics, and policy - Aswathanarayana, U.; Harikrishnan, T. (Tulsidas); Thayyib Sahini, K. M. (Kadher Mohien) (Boca Raton, FL : CRC Press)
Includes bibliographical references and indexes.